Challenging discourses of aspiration: The role of expectations and attainment in access to higher education. (19th September 2018) - Harrison, Neil; Waller, Richard
Abstract : Raising the proportion of young people from disadvantaged backgrounds progressing to higher education has been a key policy objective for successive governments in the UK since the late 1990s. Often this has been conceptualised as a problem with their 'aspirations', with the solution being seen as the provision of 'aspiration‐raising' activities to promote higher education to those thought to have the potential to progress. Recent large‐scale studies cast strong doubt on this hypothesis by demonstrating that aspirations are not generally low, that different social groups have similar levels of aspiration and that school attainment accounts for nearly all the differences in participation rates between social groups. This article draws on data from a national project exploring efforts to widen participation across two generations of practitioner‐managers in England, focusing on their conceptualisations of the field and their constructions of 'successful' activities. It uses the lens of 'possible selves' (Markus & Nurius, 1986 ) to argue that too much policy emphasis has been placed on the aspirations of young people, rather than either their academic attainment or their expectations, which are shaped by the normative expectations of the adults surrounding them. In addition, the more expansive concepts of widening participation that were present a decade ago have become less common, with a shift towards activities with a clear role in institutional recruitment rather than social transformation. The article concludes with alternative suggestions for policy and practice.